Gambaran Faktor Risiko Penyakit Tidak Menular Berdasarkan Hasil Skrining Peserta Posbindu Rosella Kembangan Selatan - Susy Olivia Lontoh; Song, Chrismerry; Ernawati Ernawati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Non-communicable diseases (NCDs) are the leading causes of morbidity and mortality, particularly among older adults. Integrated Development Posts for Non-Communicable Diseases (Pos Pembinaan Terpadu Penyakit Tidak Menular / Posbindu PTM) play a crucial role in the early detection of NCD risk factors at the community level. This activity aimed to conduct NCD risk factor screening through the measurement of blood pressure, random blood glucose, total cholesterol, and uric acid levels, as well as to provide health consultations for participants of Posbindu Rosella, South Kembangan. The activity was conducted in November 2025 using a descriptive design. A total of 30 Posbindu participants were involved. Health examinations included blood pressure, random blood glucose, total cholesterol, and uric acid measurements. Data were analyzed descriptively and classified into normal and abnormal categories based on clinical guidelines. The majority of participants were female (80%), with a mean age of 60.5 ± 9.7 years. The mean systolic blood pressure was within the hypertensive range. Approximately 50% of participants had impaired glucose regulation, 60% experienced hyperuricemia, and 40% had total cholesterol levels classified as borderline or higher. Health screening activities at Posbindu revealed a high prevalence of NCD risk factors among participants. Posbindu plays an essential role in early detection and community-based prevention of non-communicable diseases.